Perancangan Dokumen Persiapan Sertifikasi ISO 17025:2017 untuk Laboratorium Perkerasan dan Bahan Jalan - Sean Rennard Tirtawijaya; Jani Rahardjo (Jurnal Titra, 2023)
The Petra Christian University Pavement and Road Materials Laboratory requires the design of an SNI ISO 17025:2017 document. The design of the document is carried out so that the Pavement and Road Materials laboratory gets accreditation so that the test results can be recognized internationally. This research was conducted by analyzing the initial gap of the document, identifying the business process, creating the document, verifying the document, and analyzing the final gap of the document. The results of the initial gap analysis show that the Pavement and Road Materials Laboratory only has 5 documents with a percentage of 6.76%. Document creation is done by making adjustments to existing documents and designing and creating documents that do not yet exist. After the document creation process is complete, the document is verified, the results of the final document gap analysis show that the completeness of the document has increased by 72.97%. The completeness of the final documents for the Pavement and Road Materials Laboratory is 79.7% with a total of 59 documents.